Effect of Coconut Water on Seed Germination of True Seed of Shallot (TSS) Trisula and Biru Lancor Varieties - Tri Sudaryono; PER Prahardini (Indonesian Journal of Environment and Sustainable Development, 2021)
The strategy considered to increase domestic shallot production is the use of True Seed of Shallot (TSS) as a seed source for shallot cultivation. The main disadvantage of shallot cultivation with TSS as a source of seeds is the low TSS growth power, which is naturally only in the range of 50-60%. The use of growth regulators is expected to increase TSS germination. Coconut water has been reported to be a natural growth regulator. This study aimed to determine the efficacy of coconut water treatment  on the nursery phase and growth performance of TSS seedlings of Trisula and Biru Lancor varieties. The study was conducted between March to May 2018 in Pelem Village, Pare District, Kediri Regency, East Java, Indonesia. True Shallot Seeds were soaked with coconut water, seeding to polybag, and observed for  vegetative growth. The results showed that the TSS of Trisula and Biru Lancor varieties showed different responses to coconut water treatment. In the nursery phase, the use of coconut water can increase the growth power of TSS of Trisula varieties to 91%, while for the Biru Lancor variety was 72%. The use of coconut water in the Trisula variety was able to produce vegetative growth of seeds better than the Biru Lancor variety. At 5 weeks after seedling, the Trisula variety produced as many as 3.4 leaves, while the Biru Lancor variety had only 2.1 leaves. Likewise the diversity of plant height, at 5 weeks after seedling, the Trisula variety recorded a  plant height of 24.63 cm, while the Biru Lancor variety was 16.06 cm. It can be concluded that coconut water can be used as a growth regulator to increase TSS germination and increase growth performance in the nursery phase. Keywords: Shallot, True Seed of Shallot, Coconut Water, Germination, Growth Performance